Parental attitudes toward School and Chinese Adolescents' Academic Performance: A Moderated Mediation Model. (April 2022) - Ding, Fangyuan; Xiao, Xingxue; Shi, Yijun; Wan, Yani; Cheng, Gang
To explore the relationships between parents' attitudes toward school (PAS) and adolescents' family socioeconomic status (SES), psychological suzhi, and academic performance, we investigated a total of 1319 Chinese middle school students from junior grade 1 to senior grade 3 and their parents. The psychological suzhi was self-reported by students. Family SES and PAS were rated by one of the parents of the adolescents. Academic performance was collected from the final examination at school at the end of the semester. The results showed that (1) PAS were significantly negatively correlated with family SES, psychological suzhi and its components, and academic performance. Psychological suzhi and its components were significantly positively correlated with academic performance and family SES, while adolescents' academic performance was not significantly correlated with family SES. (2) Psychological suzhi and its components played partial mediating roles between PAS and academic performance. However, cognitive quality showed a positive effect on academic performance, similar to psychological suzhi, while individuality and adaptability showed the opposite effects. (3) Family SES played a moderating role in the direct paths from PAS to cognitive quality and academic performance. Our results suggest that it may be effective to improve adolescents' academic performance by improving negative PAS.